Social self-efficacy and short-term variability in social relationships: the MacArthur successful aging studies. - Lang, Frieder; Featherman, David L.; Nesselroade, John R. (Psychology and Aging, 1997)
Dealing with others entails both stability and short-term variability of the functions and outcomes of social relationships. The authors argue that patterns of short-term intraindividual variability in social relationships and self-efficacy beliefs contribute interpretable information about social adaptation. On the basis of 23 repeated weekly measurements of a sample of 32 participants ages 56 to 88 years, the authors examined the extent to which fluctuations in perceived relational outcomes are related to fluctuations of social self-efficacy. Results showed that individuals differ systematically in respect to the extent to which they experience and display fluctuations in self-efficacy and availability of social relationships. Moreover, when individuals perceive others to be available across time, social self-efficacy beliefs are stronger and fluctuate less across time.